Need Analysis on English for Specific Purposes of Visual Communication Design Student at Vocational High School - Saputro, Danang Aji; Savitri, Wiwiet Eva (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2025)
English for Specific Purposes (ESP) plays a vital role in preparing vocational students for effective workplace communication. However, many ESP programs do not fully address learners' actual needs due to the lack of a structured needs analysis. This study applies Hutchinson and Waters' (1987) framework: Target Situation Analysis (TSA), Present Situation Analysis (PSA), and Learning Situation Analysis (LSA) to examine the English language needs of Visual Communication Design (VCD) students at SMK PGRI 13 Surabaya. Employing a mixed-methods approach, data were collected from 89 students, 4 teachers, and 6 industry practitioners through questionnaires and interviews. Findings revealed that 46.5% of students identified speaking as the most essential skill, followed by reading (30.7%) and listening (13.9%), which aligns with the demands of professions such as motion graphic designer and content creator. Despite this, only 8.9% of students felt proficient in speaking, and 66.3% acknowledged their English skills were insufficient for future professional use. 44.6% reported that English was rarely integrated into their design-related subjects. Regarding learning preferences, 57.4% favoured design-based games, 54.5% preferred tutorial videos, and 63.4% were inclined toward visual materials such as infographics. These findings highlight the importance of creating a student-centred ESP curriculum that truly reflects what Visual Communication Design students need, including industry-relevant content, engaging visuals and digital media, and interactive activities to help them build their language skills and career readiness.